The multiple roles of antibiotics and antibiotic resistance in nature (2015)
Antibiotics and antibiotic resistance have most commonly been viewed in the context of human use and effects. However, both have co-existed in nature for millennia. Recently the roles of antibiotics and antibiotic resistance genes have started to be discussed in terms of functions other than bacterial inhibition and protection. This special topic will focus on both the traditional role of antibiotics as warfare mechanisms and their alternative roles and uses within nature such as antibiotics as signals or communication mechanisms, antibiotic selection at low concentrations, the non-specific role of resistance mechanisms in nature: e.g. efflux pumps, evolution of antibiotic resistance and the role of persisters in natural antibiotic resistance.